2009
DOI: 10.1111/j.1744-9987.2009.00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D as a Novel Nontraditional Risk Factor for Mortality in Hemodialysis Patients

Abstract: We examined the prevalence of vitamin D deficiency in hemodialysis patients and tested the hypothesis that decreased levels of 25-hydroxyvitamin D (25D) are associated with an increased risk for early all-cause mortality. One hundred and two patients, 57 (56%) men and 45 (44%) women, mean age 60.5 +/- 13.1 years, were included in our study. Serum calcium and phosphorus levels were measured by routine laboratory methods. Parathyroid hormone (PTH) was measured by immunoassay and 25D by enzyme immunoassay. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…16 In a previous study, the prevalence of vitamin D deficiency was examined in HD patients. 3 Patients were observed from the date of laboratory measurement until their death or up to a maximum of 730 days. 3 The study included 56% men and their mean ± SD age was 60.5 ± 13.1 years (range 23 -82 years).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…16 In a previous study, the prevalence of vitamin D deficiency was examined in HD patients. 3 Patients were observed from the date of laboratory measurement until their death or up to a maximum of 730 days. 3 The study included 56% men and their mean ± SD age was 60.5 ± 13.1 years (range 23 -82 years).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies, one of them conducted in the Department of Dialysis, University Medical Centre Maribor, Maribor, Slovenia, have examined the potential link between vitamin D deficiency and mortality in haemodialysis (HD) patients; both studies showed that decreased endogenous vitamin D levels were associated with higher allcause early mortality. 3,4 According to the Kidney Disease: Improving Global Outcomes (KDIGO) CKD-MBD Work Group, the measurement of serum 25- According to a previous study, increased mortality was observed in HD patients with 25(OH)D levels < 50 nmol/l. 3 Currently, there are no guidelines concerning vitamin D supplementation in HD patients, although guidelines for supplementation with high-dose ergocalciferol (vitamin D 2 ) in predialysis patients with CKD stages 3 and 4 are available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were divided into two groups based on 25(OH)-vitamin D levels (\50 nmol/l and [50 nmol/l). The presence of 25(OH)-vitamin D levels B50 nmol/l was associated with higher all-cause early mortality (P \ 0.033) [57]. In another trial [58], chronic hemodialysis patients receiving injectable vitamin D had a lower cardiovascular-related mortality compared with patients not receiving injectable vitamin D (P \ 0.001).…”
Section: Vitamin D and Hyperparathyroidismmentioning
confidence: 99%
“…A recent study examined the association between decreased levels of 25(OH)-vitamin D with an increased risk for early allcause mortality [57]. Patients were divided into two groups based on 25(OH)-vitamin D levels (\50 nmol/l and [50 nmol/l).…”
Section: Vitamin D and Hyperparathyroidismmentioning
confidence: 99%